2015
DOI: 10.1017/s0022215115001905
|View full text |Cite
|
Sign up to set email alerts
|

Tailed Palva flap in the subperiosteal pocket technique for cochlear implantation

Abstract: This study shows that the tailed Palva incision facilitates easy insertion of the implant and, by creating a one-way obscured pocket, this technique also enhances stabilisation of the receiver-stimulator, thereby avoiding anterior migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Two studies of the same medical center had overlapping patient cohorts. The study conducted in 2011 was excluded, because this study had the smallest number of participants (18,19). Six studies were excluded because it was unclear if the study population consisted of the minimum of 10 adult patients (20)(21)(22)(23)(24)(25).…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies of the same medical center had overlapping patient cohorts. The study conducted in 2011 was excluded, because this study had the smallest number of participants (18,19). Six studies were excluded because it was unclear if the study population consisted of the minimum of 10 adult patients (20)(21)(22)(23)(24)(25).…”
Section: Results Of Searchmentioning
confidence: 99%
“…We included five retrospective reviews (18,26,(28)(29)(30) and two prospective, nonrandomized, observational trials (31,32). Follow-up varied across the retrospective studies from 6 days to 6 years, with only two studies reporting a minimum follow-up of 12 months (26,28).…”
Section: Study Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many techniques of raising a periosteal flap have been described. Orhan et al [6] described a Tailed Palva flap technique in which the superior incision of the standard Palva flap was extended 2 cms posteriorly. Fouad et al [7] reported another modification of the Palva flap by extending the superior incision posteriorly and inferiorly to create a second inferiorly based flap.…”
Section: Resultsmentioning
confidence: 99%